Does previous application of photobiomodulation using light-emitting diodes at different energy doses modify the peak running velocity and physiological parameters? A randomized, crossover, double-blind, and placebo-controlled study - Peserico, Cecília Segabinazi (2020)
Objective: This study aimed to verify the acute effects of photobiomodulation (PBM) using different doses of LED on peak running velocity (Vpeak) and physiological parameters. Materials and methods: The study had a randomized, crossover, double-blind, and placebo-controlled format, in which 15 physically active males were submitted, besides the control (CON), to four conditions performed 5 min before the maximal incremental treadmill tests for the determination of Vpeak: placebo (PLA) and three conditions of PBM application at different doses: PBM applied with 30 J per area (PBM1), PBM applied with 120 J per area (PBM2), and PBM applied with 180 J per area (PBM3). The LED was applied using an equipment with 56 diodes of red light (660 nm; 50 mW/cm2 and 1.5 J/cm2 each diode) and 48 diodes of infrared light (850 nm; 150 mW/cm2 and 4.5 J/cm2 each diode). The PBM was applied in two regions of the quadriceps muscle, two regions of the femoral biceps muscle, and one region of the gastrocnemius muscle in both legs. Results: There was no difference among the outcomes from PBM irradiations and PLA condition for the variables, Vpeak (CON = 13.4 ± 1.6; PLA = 13.4 ± 1.6; PBM1 = 13.5 ± 1.7; PBM2 = 13.4 ± 1.6; PBM3 = 13.4 ± 1.7 km/h), similar to other variables associated with aerobic running performance analyzed during the maximal incremental treadmill tests for Vpeak determination: lactate peak, heart rate, and rating of perceived exertion. Conclusions: We concluded that the application of different doses of PBM using LEDs did not modify Vpeak and physiological and perceptual parameters.